#### Answer

6x$^3$

#### Work Step by Step

Combine like terms to simplify the expresion.
4x$^3$+2x$^3$=(4+2)x$^3$=6x$^3$

Published by
Pearson

ISBN 10:
0-13417-805-X

ISBN 13:
978-0-13417-805-9

6x$^3$

Combine like terms to simplify the expresion.
4x$^3$+2x$^3$=(4+2)x$^3$=6x$^3$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.